Positive solutions for singular semipositone boundary value problems on infinite intervals - Wang, Y.; Liu, L.; Wu, Yong Hong (Elsevier Inc., 2014)
By using the fixed point theory on a cone with a special norm and space, we discuss the existence of positive solutions for a class of semipositone boundary value problems on infinite intervals. The work improves many known results including singular and non-singular cases.